Dostoevsky's The Brothers Karamazov - Connolly, Julian W. (Reader's Guides., 2013)
Fyodor Dostoevsky's The Brothers Karamazov is unquestionably one of the greatest works of world literature. With its dramatic portrayal of a Russian family in crisis and its intense investigation into the essential questions of human existence, the novel has had a major impact on writers and thinkers across a broad range of disciplines, from psychology to religious and political philosophy. This proposed reader's guide has two major goals: to help the reader understand the place of Dostoevsky's novel in Russian and world literature, and to illuminate the writer's compelling and complex artisti.